2010
DOI: 10.1073/pnas.1006600107
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Wnt signaling by a Fer-type nonreceptor tyrosine kinase

Abstract: The Wnt signaling pathway must be properly modulated to ensure an appropriate output: pathological conditions result from either insufficient or excessive levels of Wnt signal. For example, hyperactivation of the Wnt pathway is associated with various cancers and subnormal Wnt signaling can lead to increased invasiveness of tumor cells. We found that the Caenorhabditis elegans ortholog of the Fer nonreceptor tyrosine kinase, FRK-1, limits Wnt signaling by preventing the adhesion complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…This suggests that the Wnt pathway components, such as WRM-1, might be direct targets of FRK-1 phosphorylation either in establishing export of the complex from the seam cell nuclei during POP-1 export in the posterior daughter or, perhaps, to prevent anterior accumulation of the WRM-1 in the anterior daughter. Our data are consistent with a prior study that demonstrated FRK-1 regulation of cell division within the endodermal lineage; however, that study did not test whether the endodermal proliferation influence of FRK-1 was kinase dependent (Putzke and Rothman 2010). In addition to FRK-1 in C. elegans, kinase-independent activities of Fer kinase were shown by Craig et al (2001) in which a kinase-inactivating knock-in resulted in viable mice.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This suggests that the Wnt pathway components, such as WRM-1, might be direct targets of FRK-1 phosphorylation either in establishing export of the complex from the seam cell nuclei during POP-1 export in the posterior daughter or, perhaps, to prevent anterior accumulation of the WRM-1 in the anterior daughter. Our data are consistent with a prior study that demonstrated FRK-1 regulation of cell division within the endodermal lineage; however, that study did not test whether the endodermal proliferation influence of FRK-1 was kinase dependent (Putzke and Rothman 2010). In addition to FRK-1 in C. elegans, kinase-independent activities of Fer kinase were shown by Craig et al (2001) in which a kinase-inactivating knock-in resulted in viable mice.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, it has also been reported that APR-1 is likely involved in exporting WRM-1 from the seam cell nuclei (Takeshita and Sawa 2005;Mizumoto and Sawa 2007a;Gleason and Eisenmann 2010). FRK-1 has been shown to interact with both APR-1 and WRM-1 previously in regulating cellular identity and proliferation (Putzke et al 2005;Putzke and Rothman 2010). Our data contribute significantly to these previous studies by supporting a model whereby FRK-1 facilitates POP-1 export via WRM-1.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…WRM-1 functions in a variant Wnt signaling pathway with SYS-1 and has acquired the novel function of regulation of TCF nuclear localization (described below). HMP-2 is the only protein with clear function in cell adhesion in a cadherin/ catenin complex (Costa et al 1998;Korswagen et al 2000;Natarajan et al 2001); however, recent work suggests it may also regulate Wnt signaling indirectly (Putzke and Rothman 2010;Sumiyoshi et al 2011). Thus, by having to maintain only one of the several functions of b-catenin in other species, C. elegans b-catenin proteins may have been more free to diverge in sequence after gene duplication events occurred.…”
Section: B-catenins: the More The Merriermentioning
confidence: 99%